2015
DOI: 10.12659/msm.892337
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Repetitive Transcranial Magnetic Stimulation on Post-Stroke Dysmnesia and the Role of BDNF Val66Met SNP

Abstract: BackgroundLittle is known about the effects of low-frequency repetitive transcranial magnetic stimulation (rTMS) on dysmnesia and the impact of brain nucleotide neurotrophic factor (BDNF) Val66Met single-nucleotide polymorphism (SNP). This study investigated the impact of low-frequency rTMS on post-stroke dysmnesia and the impact of BDNF Val66Met SNP.Material/MethodsForty patients with post-stroke dysmnesia were prospectively randomized into the rTMS and sham groups. BDNF Val66Met SNP was determined using rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 56 publications
2
57
0
1
Order By: Relevance
“…The results were in accordance with a previous study reporting that TMS improves executive function for patients of cerebrovascular disease with cognitive impairment (Rektorova et al, 2005). In addition, the memory improvement was inconsistent with a previous study using 1-Hz rTMS at the right DLPFC for stroke patients (Lu et al, 2015), in which they reported peripheral brain-derived neurotrophic factor (BDNF) changes as well. It is undetermined if peripheral biomarkers (e.g., BDNF) could predict the clinical improvements for the cognitive function of these patients.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The results were in accordance with a previous study reporting that TMS improves executive function for patients of cerebrovascular disease with cognitive impairment (Rektorova et al, 2005). In addition, the memory improvement was inconsistent with a previous study using 1-Hz rTMS at the right DLPFC for stroke patients (Lu et al, 2015), in which they reported peripheral brain-derived neurotrophic factor (BDNF) changes as well. It is undetermined if peripheral biomarkers (e.g., BDNF) could predict the clinical improvements for the cognitive function of these patients.…”
Section: Discussionsupporting
confidence: 63%
“…RBMT is designed to evaluate daily memory ability, which is made up of 11 subtests: remembering names, remembering hidden belongings, remembering an appointment, picture recognition, prose recall, recalling a short route, remembering an errand, orientation, and date and face recognition (Lu et al, 2015).…”
Section: Outcome Measurementsmentioning
confidence: 99%
“…In addition, evidence in recent studies has shown that rTMS may significantly improve cognitive impairment in stroke patients. For example, Lu et al showed that low-frequency rTMS improved cognitive and memory functions in patients with stroke and that this affect lasted for 2 months after treatment (Lu et al, 2015 ). Park et al used K-MMSE and LOTCA-G scores to show that cognitive functions were significantly improved by rTMS in stroke patients (Park and Yoon, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of rTMS are non-invasively and painlessly modulating the cortical excitability (excite or inhibit) of both the stimulated region and some distant regions in the brain (16), and reorganizing functional connectivity among certain regions to ameliorate brain networks (17). However, to date, there are still limited evidences on the application of rTMS for PSCI with positive results (8,18,19) and very few studies investigating the underpinnings.…”
Section: Introductionmentioning
confidence: 99%